2000
DOI: 10.1042/bj3480551
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding directly stimulates ubiquitination of the inositol 1,4,5-trisphosphate receptor

Abstract: Down-regulation of the Ins(1,4,5)P3 receptor is an adaptive response to the activation of certain phosphoinositidase C-linked cell-surface receptors. It is manifested as a profound decline in cellular Ins(1,4,5)P3 receptor content, occurs with a half-time of 0.5-2 h and is due to accelerated proteolysis. It has been shown that this process is mediated by the ubiquitin/proteasome pathway and is therefore initiated by Ins(1,4,5)P3 receptor ubiquitination. To investigate the role of ligand binding in Ins(1,4,5)P3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…260 kDa) did not co-immunoprecipitate with IP 3 R1-HA (approx. 270 kDa, long exposure; Figure 1A, lanes [11][12][13][14][15], that down-regulation of endogenous IP 3 R1 was beginning to occur (short exposure; Figure 1A, lanes 4 and 5, and, 9 and 10) and that expression of IP 3 R1-HA did not markedly increase total IP 3 R1 immunoreactivity (short exposure; Figure 1A, compare lanes 6-10 with 1-5), consistent with the relatively low transfection efficiency. Overall, these experiments indicate that exogenous IP 3 R1-HA is expressed at relatively high levels in transiently transfected αT3-1 cells and that it is ubiquitinated in response to GnRH similarly to endogenous IP 3 R1.…”
Section: Figure 2 the Properties Ubiquitination And Down-regulation mentioning
confidence: 99%
See 2 more Smart Citations
“…260 kDa) did not co-immunoprecipitate with IP 3 R1-HA (approx. 270 kDa, long exposure; Figure 1A, lanes [11][12][13][14][15], that down-regulation of endogenous IP 3 R1 was beginning to occur (short exposure; Figure 1A, lanes 4 and 5, and, 9 and 10) and that expression of IP 3 R1-HA did not markedly increase total IP 3 R1 immunoreactivity (short exposure; Figure 1A, compare lanes 6-10 with 1-5), consistent with the relatively low transfection efficiency. Overall, these experiments indicate that exogenous IP 3 R1-HA is expressed at relatively high levels in transiently transfected αT3-1 cells and that it is ubiquitinated in response to GnRH similarly to endogenous IP 3 R1.…”
Section: Figure 2 the Properties Ubiquitination And Down-regulation mentioning
confidence: 99%
“…IP 3 R1-HA was point-mutated at sites known to modify receptor properties. Arg 265 was mutated to glutamine (R265Q), since this has been reported to block IP 3 binding [21] and should allow for a more precise analysis of the role of IP 3 binding in triggering ubiquitination than that obtained from analysing deletion mutants [15]. Glu 2100 was mutated to asparagine (E2100D), since this decreases the binding affinity of Ca 2+ to the Ca 2+ sensor [5] by approx.…”
Section: Effects Of Mutations On Ip 3 R1-ha Ubiquitination and Down-rmentioning
confidence: 99%
See 1 more Smart Citation
“…In somatic cells, mutational studies have shown that IP 3 R-1 down-regulation is mediated by IP 3 binding, which induces ubiquitination and subsequent degradation by the proteasome [22]. A similar mechanism, therefore, is believed to operate in mammalian eggs [20,21].…”
Section: Introductionmentioning
confidence: 96%
“…The effect was, however, associated with (and apparently dependent upon) a GnRH-stimulated reduction in the number of Ins(1, 4, 5)P 3 -Rs (Willars et al, 2001). Sustained activation of several PLCactivating GPCRs has been shown to cause Ins(1, 4, 5)P 3 -R down-regulation by a process thought to involve a Ca 2+ -dependent proteolysis of the active Ins(1, 4, 5)P 3 -R con- formation (Wojcikiewicz & Oberdorf, 1996;Zhu & Wojcikiewicz, 2000). Although this effect is typically sluggish and modest the effect was more pronounced and rapid with GnRH-R (e.g., 80% reduction within 20-30 min).…”
Section: What Desensitisation Mechanisms Operate Down-stream Of the Gmentioning
confidence: 97%